Investigation of flocculation efficiency in treatment of wet gas treatment slime of ferroalloys production - Shkop, Andrii; Briankin, Oleksandr; Shestopalov Oleksіi; Ponomareva, Natalya (Technology audit and production reserves, 2017)
The object of research is the process of wastewater treatment from suspended solids, formed as a result of wet gas treatment of the exhaust gases of ferroalloys production shop. As a result of the audit, it is revealed that the flocculation of slimes in the current water circulation cycle scheme does not occur with due efficiency, since the dosing of the flocculant is made at one point in the slime water pipe, without adjusting its dose when the slime concentration, dispersion and chemical composition change. It is found that the gas treatment slimes have a high content of dissolved salts up to 26 g/l, a variable chemical composition and pH of 8 to 10, as well as a high proportion of fine particles of less than 40 μm in size. It is established that the peculiarities of mixing slimes with flocculant play an important role in flocculation. For effective treatment of slimes and elimination of these drawbacks, it is suggested to introduce flocculant not once but in two portions 35–40 % and 60–65 %, respectively, with a mixing time of up to 30 seconds of the first dose and about 10 seconds of the second dose. The possibilities of effective treatment of slime waters of wet gas treatment up to 0.35 g/l are established using sedimentation centrifugal plants. It is recommended to take the slime intake directly at the outlet from the ferrosilicon production shop with the solids phase fraction with a size larger than 40 μm in excess of 80 % and a concentration of up to 10 g/l.